Association between fatty acids intake and bone mineral density in adults aged 20–59: NHANES 2011–2018 - Fang, Ze-Bin; Wang, Gao-Xiang; Cai, Gui-Zhang; Zhang, Peng-Xiang; Liu, De-Liang; Chu, Shu-Fang; Li, Hui-Lin; Zhao, Hing-Xia (Frontiers in Nutrition, 2023)
Background: Previous studies have investigated the link between fatty acid intake and bone mineral density (BMD), but the results are controversial. This study aims to examine the relationship between fatty acid intake and BMD in adults aged 20–59. Methods: The association between fatty acid consumption and BMD was analyzed using a weighted multiple linear regression model with National Health and Nutrition Examination Survey data from 2011–2018. The linearity relationship and saturation value of the connection between fatty acid consumption and BMD were assessed by fitting a smooth curve and a saturation effect analysis model. Results: The study included 8942 subjects. We found a significant positive correlation between the consumption of saturated fatty acids, monounsaturated fatty acids (MUFAs), and polyunsaturated fatty acids and BMD. In subgroup analyses that were stratified by gender and race, this association was still shown to be significant. Based on the smooth curve and saturation effect analysis, we found no saturation effect for the three fatty acids and total BMD. However, there was a turning point (20.52 g/d) between MUFAs intake and BMD, and only MUFAs intake > 20.52 g/d showed a positive correlation between MUFAs and BMD. Conclusions: We found that fatty acid intake is beneficial for bone density in adults. Therefore, according to our findings, it is recommended that adults consume moderate amounts of fatty acids to ensure adequate bone mass but not metabolic diseases.